Effect of cultural practices and selected chemicals on flowering and fruit production in some mango (Mangifera indica L.) cultivars - Stassen, Pieter Jacobus Cornelius (University of Pretoria, 2013)
Thesis (DPhil (Horticulture))--University of Pretoria, 2006.